Strategi Indonesia Menghadapi Era Konstalasi Low Earth Orbit Satelit Dalam Kemungkinan Penggunannya Oleh Intelijen Asing Sebagai Alat Spionase - Satryoko, Ariesta; Runturambi, Arthur Josias Simon (Jurnal Kajian Stratejik Ketahanan Nasional, 2020)
This study aims to find out how the strategies that can be carried out by Indonesia in dealing with the era of low earth orbit (LEO) constellations in their possible use by foreign intelligence as espionage tools. The era of LEO satellite constellation is a technological development that can help human activities. However, the LEO satellite also has the potential to be used as an espionage tool that aims to obtain more in-depth information from a country. This study uses descriptive qualitative analysis methods by collecting data from literature studies, interviews, and online searches. Analysis of Indonesia's strategy that can be done in dealing with the era of LEO constellation using the theory of realism and intelligence concepts. Based on this research, the researcher found that in responding to this potential threat, the Indonesian government should implement a strategy to prevent this potential threat, namely by conducting diplomacy to other countries. This strategy can be carried out by developing research on LEO satellites and maximizing the role of Indonesian intelligence to seek information and data on the development of LEO satellite constellations in order to maintain Indonesia's national security